Electrolytic crucible material and preparation method thereof

By adopting a combined structure of stainless steel base layer, ferromolybdenum intermediate layer and carbide working layer in the electrolytic crucible, the corrosion problem of molybdenum crucible is solved, and the high service life and low production cost of the electrolytic crucible are achieved.

CN115216811BActive Publication Date: 2025-02-21XUZHOU NANFANG YONGCI MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210941266.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-08
Publication Date
2025-02-21
Estimated Expiration
2042-08-08

AI Technical Summary

Technical Problem

Existing molybdenum crucibles are prone to corrosion during the preparation of rare earth metals or rare earth alloys, resulting in short service life, excessive molybdenum content and high production costs.

Method used

The electrolytic crucible material consisting of a stainless steel base layer, a ferromolybdenum intermediate layer and a carbide working layer is used to form iron-molybdenum carbon compounds by reacting iron-molybdenum powder plasma spraying and carbon treatment agent, thereby enhancing the corrosion resistance of the crucible.

Benefits of technology

It significantly improves the service life of the electrolytic crucible, reduces production costs, and improves the quality of rare earth products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003785752130000121
    Figure BDA0003785752130000121
  • Figure BDA0003785752130000131
    Figure BDA0003785752130000131
Patent Text Reader

Abstract

The invention discloses an electrolytic crucible material and a preparation method thereof. The electrolytic crucible material is composed of a stainless steel base layer, a molybdenum-iron middle layer and a carbide working layer from the outside to the inside in sequence; wherein the material of the stainless steel base layer is stainless steel containing molybdenum; the molybdenum-iron middle layer is formed by plasma spraying of iron-molybdenum powder, wherein the iron-molybdenum powder is a powder containing iron and molybdenum; and the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with iron-molybdenum in the molybdenum-iron middle layer. The preparation method of the invention has a simple process, low production cost, is suitable for industrial production, and the prepared electrolytic crucible has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earths and relates to a material, in particular to an electrolytic crucible material and a preparation method thereof. Background Art

[0002] Electrolytic crucibles are used in the preparation of rare earth metals or rare earth alloys. Electrolytic crucibles are closely related to the production cost and product quality of rare earth metals or rare earth alloys. Electrolytic crucibles are molybdenum crucibles, which are generally divided into pure molybdenum crucibles and molybdenum alloy crucibles. Since rare earth metals or rare earth alloys are very active, they can react with metals during high-temperature processes such as smelting and glass melting. Therefore, the molybdenum crucibles used in the preparation of rare earth metals or rare earth alloys will corrode, which will seriously affect the service life of the electrolytic crucible, and will also lead to excessive molybdenum content in rare earth products and increased production costs.

[0003] CN201811525976.5 discloses a composite molybdenum crucible and its preparation method and application, which belongs to the field of refractory metal product manufacturing. The composite molybdenum crucible is composed of a base molybdenum crucible and a molybdenum carbide layer on its surface. The outer surface and / or inner surface of the composite molybdenum crucible is a molybdenum carbide layer. The surface of the composite molybdenum crucible of the invention has a dense molybdenum carbide layer generated by in-situ reaction. The composite molybdenum crucible not only retains the high strength and unbreakable characteristics of molybdenum at high temperature, but also has the characteristics of stable high-temperature chemical properties and strong high-temperature corrosion resistance of molybdenum carbide. It is suitable for preparing rare earth metals or rare earth alloys by molten salt electrolysis, which can greatly improve the service life of the crucible, save precious molybdenum metal resources, improve the product quality of rare earth metals or rare earth alloys, and reduce production costs. However, the crucible base of the composite molybdenum crucible is still molybdenum metal, there is no intermediate transition layer, and the service life is not long enough. Summary of the invention

[0004] The object of the present invention is to provide an electrolytic crucible material with a long service life in view of the above technical defects. At the same time, the present invention also provides a preparation method of the electrolytic crucible material, which has a simple process, low production cost and is suitable for industrial production. The electrolytic crucible material and the preparation method thereof of the present invention are used in industries such as rare earth recovery.

[0005] To achieve the above-mentioned purpose, the present invention provides an electrolytic crucible material, which has the following characteristics: from the outside to the inside, it is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer in sequence; wherein the material of the stainless steel base layer is stainless steel containing molybdenum; the molybdenum-iron intermediate layer is formed by plasma spraying of iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; and the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer.

[0006] Furthermore, the present invention provides an electrolytic crucible material, which may also have the following characteristics: wherein the thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:1-5:0.2-0.5.

[0007] The present invention also provides a method for preparing an electrolytic crucible material, which has the following characteristics:

[0008] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer;

[0009] Step 2: preheat the stainless steel base layer at a temperature of 200-250°C; then spray iron-molybdenum powder on the inner surface of the stainless steel base layer with plasma, and cool it naturally after spraying to obtain a molybdenum-iron intermediate layer;

[0010] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly adhered to the charcoal particles to form a carbon treatment agent; the carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1100-1150°C in a nitrogen atmosphere, the heat preservation time is 16-20h, and slowly cooled to room temperature to obtain a carbide working layer. Among them, the carbon treatment agent in contact with the molybdenum-iron intermediate layer reacts with iron-molybdenum to form an iron-molybdenum-carbon compound. Those that are not in contact do not participate in the reaction.

[0011] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in step 2, before preheating the stainless steel base layer, it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0012] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in step 2, the method for preparing the iron-molybdenum powder is: mixing molybdenum powder and iron powder to form an iron-molybdenum mixed powder; then taking polypropylene glycol, polyvinyl alcohol, methanol and the iron-molybdenum mixed powder for initial mixing, and then adding water, and continuing to mix to form a slurry; spray drying and granulating the slurry through a spray drying tower; then heating at 600-640°C for 2-4 hours, and then continuing to heat to 1400-1500°C for sintering for 2-4 hours, and finally obtaining iron-molybdenum powder.

[0013] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in the method for preparing the iron-molybdenum powder, the volume ratio of the molybdenum powder to the iron powder is 1:0.1-0.3.

[0014] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in the method for preparing the iron-molybdenum powder, the mass ratio of the polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.1-0.3:0.01-0.03:3.

[0015] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in the method for preparing the iron-molybdenum powder, the air inlet temperature of the spray drying tower is 300-360°C, and the air outlet temperature is 120-140°C.

[0016] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in step 2, the process parameters of the plasma spraying are: the main gas is argon gas, and the pressure is 0.5-0.6 MPa; the powder feeding gas is nitrogen gas, and the pressure is 0.45-0.55 MPa; the plasma spraying speed is 1800-2000 mm / min; the powder feeding gas flow rate is 6-10 L / min; the working voltage is 60-80 V; and the working current is 400-500 A.

[0017] Furthermore, the present invention provides a method for preparing an electrolytic crucible material, which may also have the following characteristics: wherein, in step three, the mass ratio of heavy oil to charcoal to aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.3-0.5:0.05-0.08:2.1-2.5:0.1.

[0018] The beneficial effects of the present invention are as follows: the present invention provides an electrolytic crucible material and a preparation method thereof, the preparation method has a simple process, low production cost, is suitable for industrial production, and the prepared electrolytic crucible has a long service life.

[0019] Specifically, the electrolytic crucible material is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. Among them, the material of the stainless steel base layer is molybdenum-containing stainless steel, and the molybdenum-iron intermediate layer is formed by plasma spraying of iron-molybdenum powder. The molybdenum in the stainless steel base layer and the molybdenum in the molybdenum-iron intermediate layer can form a bridge for the two layers of atoms to be combined, ensuring the atomic-level combination of the two layers. At the same time, the iron in the molybdenum-iron intermediate layer is dissolved into the molybdenum atomic lattice, increasing the strength and toughness of the molybdenum metal. The carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of the carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The carbide working layer has good density, and the formed iron-molybdenum-carbon compound is not only resistant to high temperatures, but also resistant to corrosion.

[0020] Among them, iron powder and molybdenum powder are made into sauce and then sprayed into granules to make the iron powder and molybdenum powder evenly distributed, and the granules are easy to spray; at the same time, polypropylene glycol, polyvinyl alcohol and methanol are mixed to form a binder and improve the fluidity of the particles. In addition, in the preparation of the carbide working layer, aluminum oxide powder, sodium carbonate and sodium chloride can promote the formation of activated carbon atmosphere by charcoal.

[0021] The advantages of the present invention include: the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer are tightly combined, the microstructure is uniform and defect-free, the bonding strength with the substrate is high, the thermal vibration resistance is strong, and the structure is stable; the service life of the crucible is more than twice that of the original molybdenum crucible; the crucible is not made of pure molybdenum, and part of the iron is used to replace the molybdenum, so the preparation cost is low; the preparation process is simple, and the thickness of the molybdenum-iron intermediate layer and the carbide working layer is easy to control. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific embodiments.

[0023] Example 1

[0024] This embodiment provides an electrolytic crucible material, which is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. The material of the stainless steel base layer is molybdenum-containing stainless steel, and the material of the stainless steel base layer in this embodiment is 0Cr17Ni12Mo2; the molybdenum-iron intermediate layer is formed by plasma spraying iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:1:0.2.

[0025] The preparation method of the electrolytic crucible material comprises the following steps:

[0026] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; then it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0027] Step 2: Preheat the stainless steel base layer at a temperature of 200°C; then use iron-molybdenum powder plasma spraying on the inner surface of the stainless steel base layer, and cool it naturally after spraying to obtain the molybdenum-iron intermediate layer. The process parameters of plasma spraying are: the main gas is argon gas, the pressure is 0.5MPa; the powder feeding gas is nitrogen gas, the pressure is 0.45MPa; the plasma spraying speed is 1800mm / min; the powder feeding gas flow rate is 6L / min; the working voltage is 60V; the working current is 400A.

[0028] The preparation method of iron-molybdenum powder is as follows: take 200-230 mesh molybdenum powder and iron powder and mix them to form iron-molybdenum mixed powder; the volume ratio of molybdenum powder to iron powder is 1:0.1. Then take polypropylene glycol, polyvinyl alcohol, methanol and iron-molybdenum mixed powder for initial mixing, then add water and continue to mix to form slurry; the mass of polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.1:0.01:3. The slurry is spray-dried and granulated by a spray drying tower; the air inlet temperature of the spray drying tower is 300°C and the air outlet temperature is 120°C. Then place it at 600°C for heating, the heat preservation time is 4 hours, and then continue to heat to 1400°C for sintering for 4 hours, and finally grind to obtain 150-270 mesh iron-molybdenum powder.

[0029] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly adhered to the charcoal particles to form a carbon treatment agent; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.3:0.05:2.1:0.1. The carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1100°C in a nitrogen atmosphere, kept warm for 20 hours, and slowly cooled to room temperature to obtain a carbide working layer.

[0030] The prepared crucible is used as a container for preparing rare earth metal neodymium by molten salt electrolysis, and its service life is 650 furnace times.

[0031] Example 2

[0032] This embodiment provides an electrolytic crucible material, which is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. The material of the stainless steel base layer is molybdenum-containing stainless steel, and the material of the stainless steel base layer in this embodiment is 0Cr17Ni12Mo2; the molybdenum-iron intermediate layer is formed by plasma spraying iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:3:0.4.

[0033] The preparation method of the electrolytic crucible material comprises the following steps:

[0034] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; then it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0035] Step 2: Preheat the stainless steel base layer at a temperature of 250°C; then use iron-molybdenum powder plasma spraying on the inner surface of the stainless steel base layer, and cool it naturally after spraying to obtain the molybdenum-iron intermediate layer. The process parameters of plasma spraying are: the main gas is argon gas, the pressure is 0.6MPa; the powder feeding gas is nitrogen gas, the pressure is 0.55MPa; the plasma spraying speed is 2000mm / min; the powder feeding gas flow rate is 10L / min; the working voltage is 80V; the working current is 500A.

[0036] The preparation method of iron-molybdenum powder is as follows: take 200-230 mesh molybdenum powder and iron powder and mix them to form iron-molybdenum mixed powder; the volume ratio of molybdenum powder to iron powder is 1:0.3. Then take polypropylene glycol, polyvinyl alcohol, methanol and iron-molybdenum mixed powder for initial mixing, then add water and continue to mix to form slurry; the mass of polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.2:0.02:3. The slurry is spray-dried and granulated by a spray drying tower; the air inlet temperature of the spray drying tower is 360°C and the air outlet temperature is 140°C. Then place it at 640°C for heating, the heat preservation time is 2 hours, and then continue to heat up to 1500°C for sintering for 2 hours, and finally grind to obtain 150-270 mesh iron-molybdenum powder.

[0037] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly adhered to the charcoal particles to form a carbon treatment agent; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.4:0.07:2.4:0.1. The carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1150°C in a nitrogen atmosphere, kept warm for 16 hours, and slowly cooled to room temperature to obtain a carbide working layer.

[0038] The prepared crucible is used as a container for preparing rare earth metal neodymium by molten salt electrolysis, and its service life is 680 furnace times.

[0039] Example 3

[0040] This embodiment provides an electrolytic crucible material, which is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. The material of the stainless steel base layer is molybdenum-containing stainless steel, and the material of the stainless steel base layer in this embodiment is 0Cr17Ni12Mo2; the molybdenum-iron intermediate layer is formed by plasma spraying iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:5:0.5.

[0041] The preparation method of the electrolytic crucible material comprises the following steps:

[0042] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; then it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0043] Step 2: Preheat the stainless steel base layer at a temperature of 220°C; then use iron-molybdenum powder plasma spraying on the inner surface of the stainless steel base layer, and cool it naturally after spraying to obtain the molybdenum-iron intermediate layer. The process parameters of plasma spraying are: the main gas is argon gas, the pressure is 0.5MPa; the powder feeding gas is nitrogen gas, the pressure is 0.5MPa; the plasma spraying speed is 1900mm / min; the powder feeding gas flow rate is 8L / min; the working voltage is 70V; the working current is 450A.

[0044] The preparation method of iron-molybdenum powder is as follows: take 200-230 mesh molybdenum powder and iron powder and mix them to form iron-molybdenum mixed powder; the volume ratio of molybdenum powder to iron powder is 1:0.2. Then take polypropylene glycol, polyvinyl alcohol, methanol and iron-molybdenum mixed powder for initial mixing, then add water and continue to mix to form slurry; the mass of polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.3:0.03:3. The slurry is spray-dried and granulated by a spray drying tower; the air inlet temperature of the spray drying tower is 330°C and the air outlet temperature is 130°C. Then place it at 620°C for heating, the insulation time is 3 hours, and then continue to heat to 1450°C for sintering for 3 hours, and finally grind to obtain 150-270 mesh iron-molybdenum powder.

[0045] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly adhered to the charcoal particles to form a carbon treatment agent; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.5:0.08:2.5:0.1. The carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1100°C in a nitrogen atmosphere, kept warm for 18 hours, and slowly cooled to room temperature to obtain a carbide working layer.

[0046] The prepared crucible is used as a container for preparing rare earth metal neodymium by molten salt electrolysis, and its service life is 670 times.

[0047] Example 4

[0048] This embodiment provides an electrolytic crucible material, which is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. The material of the stainless steel base layer is stainless steel containing molybdenum, and the material of the stainless steel base layer in this embodiment is 0Cr17Ni12Mo2; the molybdenum-iron intermediate layer is formed by plasma spraying iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:0.8:0.17.

[0049] The preparation method of the electrolytic crucible material comprises the following steps:

[0050] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; then it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0051] Step 2: Preheat the stainless steel base layer at a temperature of 200°C; then use iron-molybdenum powder plasma spraying on the inner surface of the stainless steel base layer, and cool it naturally after spraying to obtain the molybdenum-iron intermediate layer. The process parameters of plasma spraying are: the main gas is argon gas, the pressure is 0.5MPa; the powder feeding gas is nitrogen gas, the pressure is 0.45MPa; the plasma spraying speed is 1800mm / min; the powder feeding gas flow rate is 6L / min; the working voltage is 60V; the working current is 400A.

[0052] The preparation method of iron-molybdenum powder is as follows: take 200-230 mesh molybdenum powder and iron powder and mix them to form iron-molybdenum mixed powder; the volume ratio of molybdenum powder to iron powder is 1:0.1. Then take polypropylene glycol, polyvinyl alcohol, methanol and iron-molybdenum mixed powder for initial mixing, then add water and continue to mix to form slurry; the mass of polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.07:0.008:3. The slurry is spray-dried and granulated by a spray drying tower; the air inlet temperature of the spray drying tower is 300°C and the air outlet temperature is 120°C. Then place it at 600°C for heating, the heat preservation time is 4 hours, and then continue to heat up to 1400°C for sintering for 4 hours, and finally grind to obtain 150-270 mesh iron-molybdenum powder.

[0053] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly attached to the charcoal particles to form a carbon treatment agent; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.26:0.04:2.0:0.1. The carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1100°C in a nitrogen atmosphere, kept warm for 20 hours, and slowly cooled to room temperature to obtain a carbide working layer.

[0054] The prepared crucible is used as a container for preparing rare earth metal neodymium by molten salt electrolysis, and its service life is 620 furnace times.

[0055] Example 5

[0056] This embodiment provides an electrolytic crucible material, which is composed of a stainless steel base layer, a molybdenum-iron intermediate layer and a carbide working layer from the outside to the inside. The material of the stainless steel base layer is molybdenum-containing stainless steel, and the material of the stainless steel base layer in this embodiment is 0Cr17Ni12Mo2; the molybdenum-iron intermediate layer is formed by plasma spraying iron-molybdenum powder, and the iron-molybdenum powder is a powder containing iron and molybdenum; the carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of a carbon-containing carbon treatment agent with the iron-molybdenum in the molybdenum-iron intermediate layer. The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:5.5:0.6.

[0057] The preparation method of the electrolytic crucible material comprises the following steps:

[0058] Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; then it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol.

[0059] Step 2: Preheat the stainless steel base layer at a temperature of 250°C; then use iron-molybdenum powder plasma spraying on the inner surface of the stainless steel base layer, and cool it naturally after spraying to obtain the molybdenum-iron intermediate layer. The process parameters of plasma spraying are: the main gas is argon gas, the pressure is 0.6MPa; the powder feeding gas is nitrogen gas, the pressure is 0.55MPa; the plasma spraying speed is 2000mm / min; the powder feeding gas flow rate is 10L / min; the working voltage is 80V; the working current is 500A.

[0060] The preparation method of iron-molybdenum powder is as follows: take 200-230 mesh molybdenum powder and iron powder and mix them to form iron-molybdenum mixed powder; the volume ratio of molybdenum powder to iron powder is 1:0.3. Then take polypropylene glycol, polyvinyl alcohol, methanol and iron-molybdenum mixed powder for initial mixing, then add water and continue to mix to form slurry; the mass of polypropylene glycol, polyvinyl alcohol, methanol, iron-molybdenum mixed powder and water is 1:0.05:0.38:0.04:3. The slurry is spray-dried and granulated by a spray drying tower; the air inlet temperature of the spray drying tower is 360°C and the air outlet temperature is 140°C. Then place it at 640°C for heating, the heat preservation time is 2 hours, and then continue to heat up to 1500°C for sintering for 2 hours, and finally grind to obtain 150-270 mesh iron-molybdenum powder.

[0061] Step 3: Evenly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are evenly adhered to the charcoal particles to form a carbon treatment agent; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.56:0.09:2.8:0.1. The carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1150°C in a nitrogen atmosphere, kept warm for 16 hours, and slowly cooled to room temperature to obtain a carbide working layer.

[0062] The prepared crucible is used as a container for preparing rare earth metal neodymium by molten salt electrolysis, and its service life is 640 furnace times.

[0063] The service life of the crucibles prepared in the embodiments and comparative examples is shown in the following table:

[0064]

[0065]

[0066] It can be seen from the above table that the service life of the crucible prepared by the method of the present invention is significantly improved, which is of great significance for actual industrial production.

Claims

1. An electrolytic crucible material, characterized in that: From the outside to the inside, it is composed of a stainless steel base layer, a molybdenum iron intermediate layer, and a carbide working layer; Wherein, the material of the stainless steel base layer is stainless steel containing molybdenum; The molybdenum-iron intermediate layer is formed by plasma spraying of iron-molybdenum powder, wherein the iron-molybdenum powder is a powder containing iron and molybdenum; The carbide working layer is an iron-molybdenum-carbon compound formed by the reaction of the carbon-containing carbon treatment agent with the iron-molybdenum of the molybdenum-iron intermediate layer; The preparation method of the electrolytic crucible material comprises the following steps: Step 1: First, the stainless steel material is made into a crucible by plastic forming and stress relief annealing to form a stainless steel base layer; Step 2: preheat the stainless steel base layer at a temperature of 200-250°C; then spray iron-molybdenum powder on the inner surface of the stainless steel base layer with plasma, and cool it naturally after spraying to obtain a molybdenum-iron intermediate layer; The preparation method of the iron-molybdenum powder is as follows: molybdenum powder and iron powder are mixed to form an iron-molybdenum mixed powder; polypropylene glycol, polyvinyl alcohol, methanol and the iron-molybdenum mixed powder are initially mixed, and then water is added and mixed to form a slurry; the slurry is spray-dried and granulated by a spray drying tower; then heated at 600-640°C for 2-4 hours, and then the temperature is continuously raised to 1400-1500°C for sintering for 2-4 hours to obtain the iron-molybdenum powder; the volume ratio of the molybdenum powder to the iron powder is 1:0.1-0.3; the mass ratio of the polypropylene glycol, polyvinyl alcohol, methanol, the iron-molybdenum mixed powder and water is 1:0.05:0.1-0.3:0.01-0.03:3; Step 3, uniformly mix the charcoal with aluminum oxide powder, sodium carbonate and sodium chloride, then add heavy oil and continue stirring, so that the aluminum oxide powder, sodium carbonate and sodium chloride are uniformly adhered to the charcoal particles to form a carbon treatment agent; the carbon treatment agent is loaded into a stainless steel crucible with a molybdenum-iron intermediate layer, filled, and then loaded into a heat treatment furnace; heated to 1100-1150°C in a nitrogen atmosphere, the heat preservation time is 16-20h, and slowly cooled to room temperature to obtain a carbide working layer; the mass ratio of heavy oil to charcoal and aluminum oxide powder, sodium carbonate and sodium chloride is 5:0.3-0.5:0.05-0.08:2.1-2.5:0.

1.

2. The electrolytic crucible material according to claim 1, characterized in that: in, The thickness of the stainless steel base layer, the molybdenum-iron intermediate layer and the carbide working layer is 10:1-5:0.2-0.

5.

3. The electrolytic crucible material according to claim 1, characterized in that: in, In step 2, before preheating the stainless steel base layer, it is ground and polished, then cleaned with alcohol and roughened by sandblasting, and then cleaned with alcohol again.

4. The electrolytic crucible material according to claim 1, characterized in that: in, In the method for preparing the iron-molybdenum powder, the air inlet temperature of the spray drying tower is 300-360°C, and the air outlet temperature is 120-140°C.

5. The electrolytic crucible material according to claim 1, characterized in that: in, In step 2, the process parameters of the plasma spraying are: the main gas is argon, the pressure is 0.5-0.6MPa; the powder feeding gas is nitrogen, the pressure is 0.45-0.55MPa; the plasma spraying speed is 1800-2000mm / min; the powder feeding gas flow rate is 6-10L / min; the working voltage is 60-80V; and the working current is 400-500A.

Citation Information

Patent Citations

  • Composite molybdenum crucible, and preparation method and application thereof

    CN109321870A

  • Method for preparing TiC-Mo2FeB2 double hard phase cladding layer

    CN102430838A

  • Preparation method for double-layer high-strength corrosion-resistant iron-based amorphous composite coating

    CN106835132A